Experimental study of enclosure airtightness of an outdoor chamber using the pulse technique and blower door method under various leakage and wind conditions - Zheng, Xiaofeng; Mazzon, Joe; Wallis, Ian; Wood, Christopher J. (2018)
This paper introduces an experimental study of enclosure airtightness testing of an outdoor chamber using both the pulse technique and the blower door method. This investigation is a 2nd stage comparison study following the previous testing of a house-sized chamber in a sheltered environment. The outdoor chamber in this study has dimensions, approximately half that of a standard 20ft long shipping container. Multiple openings were installed into the chamber’s envelope to provide a leakage level and characteristics similar to an average UK house. Two sets of experimental tests were carried out independently at different times to investigate: a) How the pulse technique and blower door method compare on measuring enclosure airtightness of an outdoor chamber at various leakage levels; b) How the steady wind at various wind speed affects the measurement of chamber airtightness using the pulse technique. The comparison tests were performed in the chamber with various leakage levels achieved by sealing up different vents. Both blower door and pulse have given comparable results (±16%) of air permeability at 4 Pa in most testing scenarios, which is a slightly larger discrepancy than that found in the previous sheltered environment study. In the steady wind tests, the external fabric of the chamber was subjected to wind at various wind speed levels, by utilising a multi-gear portable trailer fan. Initial findings have shown that the impact of steady wind on the measurement of chamber airtightness using the pulse technique is mostly insignificant when it is under 3.5 m/s. The measured air permeability at 4 Pa (P4) at high wind speed (4 m/s - 9.5 m/s) in one direction is 16%-24% less than that measured under fan off condition in the steady wind tests.